Investigation of the deterioration of passive films in H2S-containing solutions - Wang, Zhu; Zhang, Lei; Tang, Xian; Cui, Zhao-yang; Xue, Jun-peng; Lu, Min-xu (International journal of minerals, metallurgy and materials, 2017)
The effect of H2S on the corrosion behavior of 316 L stainless steel was investigated using electrochemical methods by changing the gas condition from CO2 to H2S and then back to CO2. The presence of H2S showed an acceleration effect on the corrosion of 316 L stainless steel in comparison with CO2. The acceleration effect remained even after the complete removal of H2S by CO2, indicating that the passive film was irreversibly damaged. X-ray photoelectron spectroscopy（XPS） analysis indicated that the passive film was composed of Cr2O3, Fe2O3, and FeS2 after being immersed in H2S-containing solutions. The semiconducting property of the passive film was then investigated by using the Mott–Schottky approach. The presence of sulfides resulted in higher acceptor and donor densities and thus was responsible for the deterioration of passive films.